(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
Forensic anthropology plays a vital role in not only identification such as racial identification, sex and age but also in identification of skeleton. Various ecological, geographical and ethnical fac tors as well as age and gender determine the dimensions of human body. Cephalometry was undertaken on 1600 healthy volunteers of either sex of age group 0-40 years. The dominant head form was dolichocephalic (47.62%) followed by mesocephalic (41.31%). Brachycephalic was rare in both sexes. Male dolichocephalics predominated. The correlation between age and sex in dolichocephalic, mesocephalic, and brachycephalic was highly significant (p value <0.01). There was a preponderance of hyperleptoprosopic (39.88%) followed by leptoprosopic (30.87%). Hyperleptoprosopic males dominated. Hypereuryprosopic (1.5%) was rare. The correlation between age and sex for euryprosopic, mesoprosopic and hyperleptoprosopic was highly significant. Majority exhibited transverse frontoparietal index 70–90. Lesser number of volunteers showed a low or high transverse frontoparietal index. 76.12% individuals exhibited nasal index 50–70. 25.87% females exhibited 60–70 nasal index with larger representation by children below 10 years, whereas males (27.31%) dominated 50–60 nasal index. The correla tion between age and sex for nasal index 50–80 was found highly significant. The dominant transcraniofacial index was 80–100 represented by 71.69% individuals. The females more fre quently represented 80–90 index and males still a higher index. The correlation between age and sex for all ranges of transcraniofacial index was found highly significant. Overall, lower zygomaticofrontal index 70–80 was more frequent in males whereas a higher index 90–100 was more common in females. The correlation between zygomaticofrontal index ranging 70–100 was found highly significant. 57.12% individuals represented 70–80 zygomaticomandibular index. The correlation between age and sex for zygomaticomandibular index ranging 60–100 was found highly significant.